Review on superior strength and enhanced ductility of metallic nanomaterials. (May 2018) - Ovid'ko, I.A.; Valiev, R.Z.; Zhu, Y.T.
Abstract: Nanostructured metallic materials having nanocrystalline and ultrafine-grained structures show exceptional mechanical properties, e.g. superior strength, that are very attractive for various applications. However, superstrong metallic nanomaterials typically have low ductility at ambient temperatures, which significantly limits their applications. Nevertheless, several examples of nanostructured metals and alloys with concurrent high strength and good ductility have been reported. Such strong and ductile materials are ideal for a broad range of structural applications in transportation, medicine, energy, etc. Strong and ductile metallic nanomaterials are also important for functional applications where these properties are critical for the lifetime of nanomaterial-based devices. This article presents an overview of experimental data and theoretical concepts addressing the unique combination of superior strength and enhanced ductility of metallic nanomaterials. We consider the basic approaches and methods for simultaneously optimizing their strength and ductility, employing principal deformation mechanisms, crystallographic texture, chemical composition as well as second-phase nano-precipitates, carbon nanotubes and graphene. Examples of achieving such superior properties in industrial materials are reviewed and discussed.